2021
DOI: 10.1590/s0004-2803.202100000-20
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the Treatment of Irritable Bowel Syndrome: A Review of Cochrane Systematic Reviews

Abstract: BACKGROUND: Irritable bowel syndrome (IBS) is a complex gastrointestinal disorder, whose understanding is relatively uncertain, and the treatment guidance decision still represents a challenge. OBJECTIVE: To identify and critically appraise systematic reviews (SRs) published in the Cochrane Database of SRs (CDSR) on the effects of interventions (pharmacological and non-pharmacological) for the treatment of IBS. METHODS: The search was conducted at the Cochrane Library in May 2020. The methodological quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Traditionally, treatment of IBS focused on pharmacological medications such as laxatives, antispasmodics, and antidepressants. In recent years, however, attention has been given to dietary interventions and cognitive/emotional therapies [ 7 , 8 ]. Diets low in fermentable oligo-, di-, monosaccharides, and polyols (FODMAPs) have gained importance and have been proposed as a first-line dietary therapy in IBS management [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, treatment of IBS focused on pharmacological medications such as laxatives, antispasmodics, and antidepressants. In recent years, however, attention has been given to dietary interventions and cognitive/emotional therapies [ 7 , 8 ]. Diets low in fermentable oligo-, di-, monosaccharides, and polyols (FODMAPs) have gained importance and have been proposed as a first-line dietary therapy in IBS management [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…They included two RCTs including 306 patients with an odds ratio of 0.94 in those administered escitalopram and p<0.05 [13,14]; four systematic reviews each studying six to 15 RCTs with greater significance and low risk of bias [9,[15][16][17] and two meta-analyses [5,10]. One of which included seven RCTs with 346 patients comparing SSRI treatment with placebo treatment and showed that 54.5% (96/176) patients with SSRI trial demonstrated improvement in their symptoms (I²=49%, p=0.07) [5].…”
Section: Resultsmentioning
confidence: 99%
“…This study only includes pain symptoms and cannot provide conclusive evidence for the relief of global symptoms of IBS. Scaciota et al published data emphasizing the efficacy of antidepressants (TCAs and SSRIs) in IBS in their systematic review [ 17 ]. They studied 15 RCTs, of which 11 RCTs with 750 subjects were interpreted for an overall assessment of relief, and the results were RR=1.57, 95% CI=1.23-2.0.…”
Section: Reviewmentioning
confidence: 99%
“…2 Proposed mechanisms of IBS include psychological factors, miscommunication between the gut and central nervous system, dysmotility, altered mucosal immune and inflammatory function, genetic susceptibility, infection and gastroenteritis, alterations in gut microbiota and visceral hypersensitivity. [3][4][5] A recent survey estimated an IBS prevalence of 3.5% in Australia and 4.1% globally. 6 It is more prevalent in women, particularly those aged 18-39 years.…”
Section: Discussionmentioning
confidence: 99%